Biocompatibilidade da terapia fotodinâmica: estudo in vitro e in vivo - Santos, Ludmilla Mota da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Introduction: Photodynamic therapy (PDT) is based on a set of biological, physical and chemical processes that occurs through the activation of a photosensitizer (PS) with light (laser or LED) to destroy target cells. The aim of this study was to evaluate the cytotoxicity and tissue response of PDT including the production of cytokines (IL - 1β and IL - 6). Methods: 1) For the cytotoxicity test groups were divided into: 5% sodium hypochlorite; 2.5% sodium hypochlorite; 2% chlorhexidine; saline; PDT (curcumin + Led blue light); and control (culture medium). The solutions were diluted in DMEM culture medium (1x104 cells) and placed in 24 -well plates with mouse fibroblast line (L929). After 6, 24 and 48 hours, the MTT assay was used to assess cell viability and ELISA assay was used to assess cytokine in the supernatant. 2) To test the tissue response, the groups were divided into: control (saline); 2.5%; sodium hypochlorite, 5% sodium hypochlorite; 2% chlorhexidine; TFD (curcumin + Led blue light). The solutions were placed into polyethylene tubes and implanted in the dorsal tissue of Wistar rats for 7, 15, 30, 60, and 90 days. The tubes were removed with surrounding tissue and divided in half and one half was stained with hematoxylin and eosin and the other half used to assess cytokine by ELISA. Statistical analysis was performed using ANOVA, Kruskal Wallis or Tukey test (p < 0.05). Results: For the in vitro study, PDT and saline showed low cytotoxicity similar to the control group (p > 0.05) , less than sodium hypochlorite (2.5% and 5%) and 2% chlorhexidine (p < 0.05) at all time periods. All solutions released cytokines similar to control (p > 0.05) amount. As for the in vivo study, all solutions caused severe inflammatory reaction after 7 days, which decreased with time. No inflammation was observed at 90 days in the PDT group similar to the control (p > 0.05) . All materials...

Introdução: A terapia fotodinâmica (TFD) se baseia em um conjunto de processos biológicos, físicos e químicos que ocorre por meio da ativação de um fotossensibilizador (FS) com luz (laser ou LED) para destruir as células alvo. O objetivo deste estudo foi avaliar a citotoxicidade e a resposta tecidual da TFD incluindo a produção de citocinas (IL - 1β e IL - 6). Métodos: 1) Para o teste de citotoxicidade os grupos foram divididos em: hipoclorito de sódio 5%; hipoclorito de sódio 2,5%; clorexidina 2%; solução salina; TFD (curcumina + luz Led azul); e controle (meio de cultura). As soluções foram diluídas em meio de cultura DMEM (1x104 células) e colocadas em placas de 24 poços, com linhagem de fibroblastos de camundongos (L-929). Depois de 6, 24 e 48 horas, o ensaio de MTT foi utilizado para avaliar a viabilidade celular e o ensaio de ELISA foi utilizado para avaliação de citocinas no sobrenadante. 2) Para o teste de resposta tecidual, os grupos foram divididos em: controle (solução salina); hipoclorito de sódio 2,5%; hipoclorito de sódio 5%; clorexidina 2%; TFD (curcumina + luz Led Azul). As soluções foram colocadas em tubos de polietileno e foram implantadas no tecido conjuntivo dorsal de ratos Wistar por 7, 15, 30, 60, e 90 dias. Os tubos com tecido circundante foram removidos e divididos ao meio e uma das metades foi corada com hematoxilina e eosina e a outra metade utilizada para avaliação das citocinas por ELISA. A análise estatística foi realizada utilizando ANOVA, Kruskal Wallis ou teste de Tukey (p < 0,05). Resultados: Quanto ao estudo in vitro, a TFD e a solução salina apresentaram baixa citotoxicidade semelhante ao do grupo controle (p> 0,05), menor que o hipoclorito de sódio (2,5% e 5%) e a clorexidina 2% (p < 0,05) em todos os períodos de tempo. Todas as soluções liberaram citocinas em quantidade similar...
Keywords: Fotoquimioterapia; Tratamento do canal radicular; Canal radicular - Irrigantes; Photochemotherapy